Effect Of Geometric Shape On The Crushing Performance Of Natural Jute Mat/Epoxy Specimens Under Axial Quasi-Static Compression - Salim Hamza, Sabah; Yaakob, Mohd Yuhazri; Al Emran, Ismail; Al Absi, Salih Emri (Transstellar Journal Publications and Research Consultancy Private Limited (TJPRC), 2020)
The interest in the using of natural composite has been increased significantly in recent years in many engineering fields due to their distinctive characteristics; these as low weights, high-energy dissipation ability, and it's considered ecofriendly. In this paper, an experimental investigation is done on the effect of structure geometry on the crashworthiness characteristics of woven jute mat/epoxy composite specimens. The main objective is to understand the influence of the geometrical shape, and layers numbers on the energy absorption of composite specimens under uniaxial quasi-static loading. The twelve hollow specimens were manufactured by combination of manual lay-up and vacuum bladder moulding technique using bi-directional natural jute mat (with two and three layers) and epoxy resin, each with 50mm inner diameter and 100mm length. Three different cross-sectional shapes were used; the hexagonal, octagonal, and decagonal of specimens. From the current unique experiment, it was exhibited most of the composite samples demonstrated stable and progressive deformation with acceptable repeatability during the test process. It also showed that the deformation characteristics and the energy absorption of the octagonal cross-section shape are better than the other cross-section shapes such as hexagonal and decagonal cross-sections shapes. Furthermore, the three laminated layers contributed to high specific energy absorption (SE) and better crushing efficiency (ɳc) for each profile. Overall, the octagonal pattern configuration with three plies can be considered as optimal for crashworthiness of structure application compared to other composite samples.